Extended diagnosis of the type species of Pseudogonatodes Ruthven 1915 (Gekkota: Sphaerodactylidae) - Montes-Correa, Andrés Camilo; Saboyá-Acosta, Liliana P.; Jiménez-Bolaño, Juan David; Angarita-Sierra, Teddy; Briceño-Pérez, Vladimir; Núñez, Samuel; Renjifo, Juan Manuel; Schargel, Walter E.; Daza, Juan D.; Hoogmoed, Marinus S. (Zootaxa, 2021)
Pseudogonatodes furvus is an endemic gecko from the region of the Sierra Nevada de Santa Marta, an isolated massif located in the continental Caribbean region of Colombia. Pseudogonatodes furvus is the type species of the genus, and its morphology and natural history remain poorly known. This lizard was described based on two specimens. After its description, the species has only been mentioned in a handful of taxonomic studies of Pseudogonatodes, in which a few morphological characters of P. furvus have been mentioned. One other paper reported two new localities, without providing new information on the external morphology, especially the lepidosis of the newly obtained specimens. Here we review the external morphology of P. furvus, based on examination of the holotype and six additional specimens. We provide an extended diagnosis and definition, description of holotype, variation, comparisons with other Pseudogonatodes, geographic distribution (adding a fourth locality to the known distribution for the species), and conservation status. Additionally, we describe osteological features for the diagnosis of the genus.